Asset Lantung : Wara-Wara Akuntabilitas dan Ghost shopping dengan Pendekatan Netnografi - Alfiyatul Qomariyah; Sultan Syah; Sri Rahayu Syah (Universitas Trunojoyo Madura, 2023)
Accountability is based on the need for an individual or entity to be able to express their anger over any day-to-day currency actions, decisions, or ex-penses that relate to them. Recognition is essential in the context of oil as-sets and natural resources to ensure that proper management and utiliza-tion are carried out. The study aims to provide an understanding of an ac-countability practice for managing Lantung assets (natural resource assets). This research uses an interpretive paradigm and qualitative method with Combination of Literature Study and Netnography Approaches. The re-sults of the study provide an understanding of accountability practices in-dicating that companies take various steps to secure their position from var-ious threats while maintaining their